Utilización de residuos agroindustriales en el cultivo de lombriz roja californiana (Elsenia foetida). - Vera Bastidas, Cristian Darío (2013)
This research was conducted in productive educational program at the Experimental Farm Vermiculture "La Maria", State Technical University of Quevedo, located at Km 7 Via Quevedo - The Junction, Canton Mocache is located between the geographical coordinates of 01 º 06 '20 "South latitude and 79 º 29' 23" west longitude at a height of 73 meters. The investigation lasted four months. The general objective was to evaluate the production, chemical and biological composition of humus obtained by the Californian red worm (Eisenia foetida), with the use of agroindustrial residues. Five treatments were studied under a completely randomized design (CRD) with 4 replicates per treatment and each repeat forming an experimental unit. The results were: Increased production of humus, the best feed conversion of organic matter to humus, the highest percentage in what has to do with organic matter and macro elements such as P, Ca, Mg and S, the treatment reported 0, (100% cattle manure). The highest concentration of fungi (Penicillium sp. T0 treatment (100% cattle manure) who showed the higher costs, the highest gross income and the best cost / benefit ratio for treatment, the treatment was recorded in T0 (100% manure Bovine). Greater utility was obtained with treatment treatment T0 (100% of cattle manure) with 99.61 dollars, this factor is due to that this treatment had a higher production of humus, rejecting the hypothesis "at least one of the treatments with agro-industrial waste presents better relationship benefited cost."